Differential rock uplift along the northeastern margin of the Tibetan Plateau inferred from bedrock channel longitudinal profiles. (January 2019) - Li, Qiong; Pan, Baotian; Gao, Hongshan; Wen, Zhenglin; Hu, Xiaofei
Highlights: Key parameters are calibrated in the shear-stress bedrock-incision model. Differential rock uplift rates are inferred from bedrock channel longitudinal profiles. Tectonic deformation pattern and controlling factors are explored in active orogen. Abstract: Bedrock channel profile analysis is a robust reconnaissance tool for examining the rates and patterns of deformation in active orogens. Here, steepness and concavity indices were extracted from bedrock channels draining the northern Qilian Mountains based on the universal shear stress incision model. The profile analysis reveals a systematic spatial distribution of steepness and concavity indices. The average steepness index for channels draining the western part is approximately 1.6 times higher than that for the eastern part. Through empirical calibration of erosion coefficient K, the influence of channel width, rock strength, discharge and sediment flux are identified, and an approximately 1.1–1.2 times difference in K values is found between the west and east under the hypothesis that lithologic resistance and sediment flux have no contribution. Correlating profile analyses with parameter calibration, an approximate 2–3 times increase in the rock uplift rate is found from the eastern part to the western part of the orogen. The integration of this study with previous work in the eastern part of the mountains indicates that cross-strike (2–4 times) and along-strike (2–3 times) differential rock uplift both exist in the northeastern margin of the Tibetan Plateau. In addition, the abnormal values of concavity are apparently associated with the channels transecting large thrust fault zones. Thus, the shortening deformation may play a dominant role in controlling the differential rock uplift through folding and thrusting of the northeast-directed thrust faults across the northeastern margin of the Tibetan Plateau.